2013
DOI: 10.15376/biores.8.3.4283-4287
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Initial Moisture Content on the Drying Process of Wood Exposed to Infrared Radiation

Abstract: This article reports the results of temperature measurements carried out on 50-mm-thick Norway spruce (Picea abies [L.] Karst) wood samples exposed to infrared (IR) radiation. The varied property with respect to the optimization of the drying technology was the initial moisture content of samples. During the experiments, temperature profiles were registered on the surface and in the core of the samples under controlled technological conditions. Based on our osmotic approach, the variability in the curves was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…The vacuum drying also led to a high temperature, the high-pressure difference between the center and the surface of the product and incremented the drying rate; this will enhance the mass transfer, hence increasing the wood's defect ratio. Similar results were reported by the other researchers using a vacuum dryer and various experiments for drying pine [3], Norway spruce [7], jujube powder [11] and almond kernels [12]. 3) to find the value, the results are shown in Table 7.…”
Section: Wood's Defects (%)supporting
confidence: 81%
See 1 more Smart Citation
“…The vacuum drying also led to a high temperature, the high-pressure difference between the center and the surface of the product and incremented the drying rate; this will enhance the mass transfer, hence increasing the wood's defect ratio. Similar results were reported by the other researchers using a vacuum dryer and various experiments for drying pine [3], Norway spruce [7], jujube powder [11] and almond kernels [12]. 3) to find the value, the results are shown in Table 7.…”
Section: Wood's Defects (%)supporting
confidence: 81%
“…Besides, the vacuum infrared drying methods, infrared (IR) irradiation is also used by Kollmann et al [5] or set up complex drying processes Altun et al [6]. In earlier work Caserta et al [7] the mechanism of wood drying by infrared radiation was studied. The results showed that the moisture migration mechanism could be considered a semipermeable process with the moisture being a dilute aqueous solution.…”
Section: Introductionmentioning
confidence: 99%